Difference of Mistakes Reflective-Impulsive Students In Mathematical Problem Solving - Dwi Noviani Sulisawati; Lutfiyah Lutfiyah; Frida Murtinasari (International Journal of Trends in Mathematics Education Research, 2019)
Mathematics is one of the important subjects in realizing the goals of education in Indonesia. However, in reality there are many students who have different problem solving abilities between one and the other and many students make mistakes when solving problems. The mistakes that are often carried out by students can also be influenced by differences in learning styles possessed. Therefore this article aims to describe differences in errors made by reflective-impulsive students in solving mathematical problems. This research is a qualitative descriptive that involving 2 research subjects with each subject having a different learning style. This research was conducted in class VII Pakusari Jember 1 Junior High School in the academic year of 2018/2019. The results of data analysis showed that differences in mistakes made by junior high school students with reflective-impulsive learning styles in solving mathematical problems were located at the stage of determining mathematical models and at the stage of completing mathematical models that had been made with the percentage of impulsive learning styles when compared to a subject that is reflective learning style.